Photobiomodulation Promotes Repair Following Spinal Cord Injury by Regulating the Transformation of A1/A2 Reactive Astrocytes - Wang, Xuankang; Zhang, Zhihao; Zhu, Zhijie; Liang, Zhuowen; Zuo, Xiaoshuang; Ju, Cheng; Song, Zhiwen; Li, Xin; Hu, Xueyu; Wang, Zhe (Frontiers in Neuroscience, 2021)
Reactive astrocytes can be classified into two distinctive phenotypes after spinal cord injury (SCI) according to their different functions: neurotoxic phenotype (A1) and neuroprotective phenotype (A2). Our previous studies proved that photobiomodulation (PBM) can promote motor function recovery and improve tissue repair after SCI, but little is known about the underlying mechanism. Therefore, we aimed to investigate whether PBM contributes to repair after SCI by regulating the activation of astrocytes. PBM was performed in clip-compression SCI male rats for two consecutive weeks, and the results showed that recovery of motor function was improved, the lesion cavity was reduced, and the number of neurons retained was increased. We determined the time course of A1/A2 astrocyte activation after SCI by RNA sequencing (RNA-Seq) and verified that PBM inhibited A1 astrocyte activation and promoted A2 astrocyte activation at 7 days post-injury (dpi) and 14 dpi. Subsequently, potential signaling pathways related to A1/A2 activation were selected by GO function analysis and KEGG pathway analysis and then examined in animal experiments and preliminarily tested in astrocyte culture conditions. Next, we observed that the expression of fibroblast growth factor (FGF) and transforming growth factor-β (TGF-β) was upregulated by PBM, and both contributed to the transformation of A1/A2 activation in a dose-dependent manner. Finally, we found that PBM reduced the neurotoxicity of A1 astrocytes to dorsal root ganglion (DRG) neurons. In conclusion, PBM can promote better recovery after SCI, which may be related to the transformation of A1/A2 reactive astrocytes.